Case Report and Literature Review: Bacterial Meningoencephalitis or Not? Naegleria fowleri Related Primary Amoebic Meningoencephalitis in China - Wenjuan Zhou; Yuzhen Ouyang; Yuzhen Ouyang; Di Zhang; Sheng Liao; Sheng Liao; Hui Liang; Hui Liang; Lingling Zhao; Chunyuan Chen (Frontiers Media S.A., 2022)
In China, a 9-year-old boy was transferred to the hospital with fever, vomiting, and headache. The disease rapidly deteriorated into vague consciousness. Applying conventional clinical examinations such as blood and cerebrospinal fluid (CSF) tests, the diagnosis of bacterial meningoencephalitis was first drawn, and expectant treatments were adopted immediately. However, the symptoms did not alleviate, adversely, this boy died 3 days after admission. Considering the skeptical points of the duration, such as the unknown infectious bacteria and the pathogen invasion path, blood and CSF samples were then sent for metagenomic next-generation sequencing (mNGS) to ascertain the cause of death. The 42,899 and 1,337 specific sequences of N. fowleri were detected by mNGS in the CSF sample and the blood sample, respectively. PCR results and pathological smear subsequently confirmed the mNGS detection. The patient was finally diagnosed as primary amoebic meningoencephalitis. Besides, in this article, 15 similar child infection cases in the past 10 years are summarized and analyzed to promote the early diagnosis of this rare disease.